Effect of light exposure on secondary metabolites production of an endophytic fungus Arthrinium rasikravindrae and its antioxidant and anticancer activities - Andita Eltivitasari; Rahmawati Rahmawati; Baiq Maylinda Gemantari; Fitra Romadhonsyah; Arief Nurrochmad; Subagus Wahyuono; Puji Astuti (Society for Indonesian Biodiversity, 2021)
Abstract. Eltivitasari A, Rahmawati, Gemantari BM, Romadhonsyah F, Nurrochmad A, Wahyuono S, Astuti P. 2021. Effect of light exposure on secondary metabolites production of an endophytic fungus Arthrinium rasikravindrae and its antioxidant and anticancer activities. Biodiversitas 22: 3156-3163. Endophytic microorganisms are one of the promising sources in producing bioactive compounds, to be developed for new drug candidates. They are found to have the ability to generate the same compounds as their host plant. Metabolite producing capacity of the endophytes is known to be affected by light exposure during fermentation process. This study focused on an endophytic fungus Arthrinium rasikravindrae isolated from Coleus amboinicus stem to reveal out its metabolite profiles due to light exposure as well as its bioactivity consequences. A. rasikravindrae was cultured on potato dextrose broth medium for 14 days and fermented in dark and exposed to natural light. Metabolite profiling was performed using TLC and GC-MS analysis. The activities were observed using DPPH assay for antioxidant and MTT assay for cytotoxicity potential. The results showed that A. rasikravindrae ethyl acetate extract produced during dark and exposed to light fermentation conditions contained different compounds but there was some which showed similarity with their host plant. Methyl octadec-9-enoate was found in all fermentation conditions as well as in C. amboinicus stem extract. Besides methyl octadec-9-enoate, methyl palmitate was also found present in both A. rasikravindrae extract fermented exposed to light and its host plant. The antioxidant activity of extract generated from dark fermentation condition was better as compared to that exposed to light with IC50 value of 66.36±0.53 vs 556.92±34.37 µg/mL. However, cytotoxic activity screening against several cancer cell lines exhibited opposing results in which extract from light-exposed fermentation resulted in better cytotoxic activity (IC50 value of 291.40 ± 2.34 µg/mL on WiDr, 336.80 ± 5.05 µg/mL on T47D, and 404.73 ± 3.46 µg/mL on Hela cell lines). Extract obtained from dark fermentation condition showed IC50 value of more than 500 µg/mL in all tested cancer cell lines. Preliminary examination on cytotoxic activity against WiDR cells suggested that the extract from light-exposed fermentation might induce cell death through mechanisms involving cell cycle arrest.